2009
DOI: 10.1016/j.dnarep.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of the genes encoding NTH1 and NEIL1 DNA N-glycosylases reveals the existence of novel carcinogenic oxidative damage to DNA

Abstract: We have generated a strain of mice lacking two DNA N-glycosylases of base excision repair (BER), NTH1 and NEIL1, homologs of bacterial Nth (endonuclease three) and Nei (endonuclease eight). Although these enzymes remove several oxidized bases from DNA, they do not remove the well-known carcinogenic oxidation product of guanine: 7,8-dihydro-8-oxoguanine (8-OH-Gua), which is removed by another DNA N-glycosylase, OGG1. The Nth1−/−Neil1−/− mice developed pulmonary and hepatocellular tumors in much higher incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
115
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(126 citation statements)
references
References 43 publications
9
115
0
2
Order By: Relevance
“…30 NEIL1 and NEIL1/NTH1 double knockout mice developed pulmonary and hepatocellular tumors. 31 Genetic alterations of the NEIL1 gene in human gastric cancer lead to impaired DNA glycosylase activity or a truncated protein. 32 Furthermore, NEIL1 has been shown to interact with other DNA repair genes which have been linked to cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 NEIL1 and NEIL1/NTH1 double knockout mice developed pulmonary and hepatocellular tumors. 31 Genetic alterations of the NEIL1 gene in human gastric cancer lead to impaired DNA glycosylase activity or a truncated protein. 32 Furthermore, NEIL1 has been shown to interact with other DNA repair genes which have been linked to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…32 Furthermore, NEIL1 has been shown to interact with other DNA repair genes which have been linked to cancer. 31,33,34 The level of NEIL1 is greatly diminished in cells depleted for FANC proteins and Fanconi anemia cell lines. Expression of the NEIL1 protein partially reverses the hypersensitivity of Fanconi anemia cells to interstrand crosslinks.…”
Section: Discussionmentioning
confidence: 99%
“…The four DNA glycosylases each function in the suppression of mutations by 8-oxo-Gua in DNA. The overlapped recognition of 8-oxo-Gua could explain the fact that single knock-out mice deficient in OGG1, MUTYH, NTH1, and NEIL1 show few tumor phenotypes [57,[65][66][67][68][69][70][71]. In contrast, there is evidence to support the view that polymorphisms in these DNA glycosylases are associated with human carcinogenesis (reviewed in 72).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cell culture studies have indicated that knock down of Neil1 renders cells more sensitive to oxidative stress, such as that induced by glucose oxidase or gamma irradiation [Rosenquist et al, 2003;Maiti et al, 2008]. NEIL1-deficient mice, although initially expected to display a promutagenic phenotype, have not been found to be significantly prone to spontaneous tumor formation, although lung adenomas and hepatocellular carcinomas have been documented in about 10-20% of aged animals [Chan et al, 2009]. A potential explanation for this lack of a cancer phenotype is overlapping substrate specificity with other NEIL isoforms or with NTH1, as discussed above.…”
Section: Actions Of Ber Glycosylases In Disease States Obesity and Mementioning
confidence: 99%
“…A potential explanation for this lack of a cancer phenotype is overlapping substrate specificity with other NEIL isoforms or with NTH1, as discussed above. Indeed, Neil1 2/2 ; Nth1 2/2 double knockout mice have been shown to develop spontaneous pulmonary adenomas and carcinomas after the first year of life at much higher rates than WT counterparts [Chan et al, 2009]. Additionally, Neil1 2/2 ; Nth1 2/2 mice also developed hepatocellular carcinomas at higher rates than WT or Nth1 2/2 mice [Chan et al, 2009].…”
Section: Actions Of Ber Glycosylases In Disease States Obesity and Mementioning
confidence: 99%